ILAI ETIKA DALAM KALÃLAH WA DIMNAH Karya Ibn al-Muqaffaâ - Puriyadi, Puriyadi (Jurnal Ilmiah Ilmu Ushuluddin, 2010)
The study of ethics as a philosophical subject has been rare in Islamic tradi-tion compared to other subjects. It is in this context that a study of ethicscontained in Ibn al-Muqaffaâs KalÃ®lah wa Dimnah is very important. ForIbn al-Muqaffaâ, the position of ethics is higher than religion itself. Thus,one should do a good thing, even though religion does not command it. Heargues that to live a life in accordance with moral values will lead a personto happiness and dignity. It is significant that he uses fables to communi-cate his ethical ideas. Through fables, he can persuade people to use not onlyreason, but also emotion and imagination, to understand ethics.